1985
DOI: 10.1002/1097-0142(19851101)56:9<2235::aid-cncr2820560917>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal carcinoma metastatic to the stomach. A clinicopathologic study of 35 cases

Abstract: Esophageal carcinoma metastatic to the stomach was analyzed in 35 patients. Ten were discovered in surgical specimens and 25 at autopsy. All patients were men with a mean age of 62 years. Primary lesions were most frequently located in the middle of thoracic esophagus and were larger than 7 cm. Undifferentiated carcinoma was found in 29% of the patients. Local spread of the primary lesions to neighboring structures was seen in 34%. Lymphatic invasion, and intramural metastases within the esophagus, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
44
1
5

Year Published

1989
1989
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 12 publications
3
44
1
5
Order By: Relevance
“…The degree to which the stomach is compromised by metastases from esophageal cancer has been described in a series of necropsies [3,8,[21][22][23][24], and the percentage rate has been progressively increasing, ranging from 2.4% to 15.2%. The significant number of cases reported in surgical specimens from patients who had undergone operation in Japan is really noteworthy [7,8,[25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The degree to which the stomach is compromised by metastases from esophageal cancer has been described in a series of necropsies [3,8,[21][22][23][24], and the percentage rate has been progressively increasing, ranging from 2.4% to 15.2%. The significant number of cases reported in surgical specimens from patients who had undergone operation in Japan is really noteworthy [7,8,[25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…The significant number of cases reported in surgical specimens from patients who had undergone operation in Japan is really noteworthy [7,8,[25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] Our previous study classified gastric involvement by esophageal squamous cell carcinoma pathologically into the following four patterns: (1) gastric invasion from metastatic lymph nodes, (2) intramural metastasis, (3) direct gastric wall involvement by the primary tumor, and (4) intraepithelial spread to the gastric mucosa. 4 Another study reported detection of IGMs in 8/274 (2.9%) patients at autopsy, none of whom had had any evidence of gastric tumors when operated upon while still alive.…”
Section: Discussionmentioning
confidence: 99%
“…However, intramural gastric metastasis (IGM) is rare, the incidence in surgical specimens being 1% to 4.58%. [1][2][3][4][5][6] It is not unusual for rapidly growing IGMs to be larger than their primary esophageal carcinomas. IGMs have an extremely poor prognosis.…”
mentioning
confidence: 99%